Perlindungan Hukum Terhadap Dokter Yang Diduga Melakukan Malpraktik Ditinjau dari Peraturan Perundang-Undangan Yang Berlaku Studi Kasus Putusan Mahkamah Agung Nomor 233 K/Pid.Sus/2021 - Christian Elizar; Markoni Markoni; I Made Kantikha; Saragih Saragih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Doctors cannot avoid the possibility of disabled patients even dying, even though in practice they are in accordance with professional standards and standard operational procedures based on patient health needs. This situation should be referred to as a medical risk, but it is often interpreted by parties outside the medical profession as malpractice, so an understanding of legal protection for doctors suspected of malpractice is needed in terms of applicable laws and regulations. By looking at the decision of the Supreme Court Number 233 K / PID. SUS/2021, even though found guilty, the Defendant cannot be charged under the Criminal Code because it has been regulated in Law Number 17 of 2023 concerning Health (Health Law) and Law Number 29 of 2004 concerning Medical Practice (Law on Medical Practice), thus affirming the existence of legal protection from laws that specifically regulate the practice of medicine. This study aims to analyze legal liability for doctors who commit malpractice, and analyze legal protection for doctors suspected of malpractice in terms of applicable laws and regulations. The research method is carried out in a normative juridical manner with statutory approach methods, conceptual approaches, and case approaches. As a result of the research, the principle of justice is not accommodated in the claim for accountability under Article 79 letter c of the Medical Practice Law. The Health Act has preventive and repressive means of protection. The defendant did not carry out his practice in accordance with the standards of the medical profession, and the standard of operational procedures and health needs of patients, so automatically medical ethics were violated, causing the defendant to be held accountable for his actions in disciplinary law, civil law, and criminal law. In order to be protected from legal liability, doctors must always carry out their practices in accordance with professional standards, and standard operational procedures based on patient health needs.